ЕТАПИ СТАНОВЛЕННЯ ТА РОЗВИТКУ МЕДІА-ПЕДАГОГІКИ У РЕСПУБЛІЦІ ПОЛЬЩА - Moroz, Olga (Continuing Professional Education: Theory and Practice, 2019)
The pre-conditions of media pedagogy development in the Republic of Poland are considered in the article; the stages of the formation and development of the media pedagogy in the scientifi c space of Poland (the origin of the ideas in media pedagogy; the creation of the research and development centers; the development of the media pedagogy as the study of the professional training) are grounded.